The Significant Relationship between Duration and Fasting Blood Glucose Level to Diabetic Neuropathy in Type-2 Diabetes Mellitus Patients - Kamila Aisyah; Nurma Yuliyanasari; Laily Irfana; Detti Nur Irawati (Universitas Muhammadiyah Surabaya, 2026)
Patients with diabetes may develop diabetic neuropathy, which damages peripheral nerves and impairs distal sensation. This study's aim was to determine the relationship between duration and fasting blood glucose with diabetic neuropathy. Patients with diabetes mellitus at Siti Khodijah Hospital in Sidoarjo, East Java, participated in this cross-sectional study. Fifty-one individuals were gathered using purposive sampling. The tools utilized were the Michigan Neuropathy Screening Instrument (MNSI) and a clinical chemistry laboratory examination—logistic regression for multivariate analysis and the contingency coefficient test for bivariate data analysis. Most type-2 DM patients who experienced diabetic neuropathy had a duration of DM >5 years (35.3%) and had fasting blood sugar levels ≥126 mg/dl (41.2%). Bivariate analysis of duration obtained a value (p = 0.003), and fasting blood sugar levels obtained a value (p = 0.000). Multivariate data analysis using logistic regression duration obtained value (Exp (B) = 22.386), and fasting blood sugar levels obtained value (Exp (B) = 35.305). There was a significant relationship between duration and fasting blood glucose levels on the incidence of diabetic neuropathy. The factor that had a higher risk of diabetic neuropathy was fasting blood sugar levels than the duration of DM.